Sosialisasi Bank Sampah Sebagai Strategi Penguatan Partisipasi Masyarakat Desa Punan Dulau Kecamatan Sekatak Kabupaten Bulungan: Pengabdian - Kartini Maharani Abdul; Iskandar; Wempi Feber; Budi Mulyadi; Irsyad Sudirman; Jimmy Nasroen; Masruri; Syaini; K. Rapiandi Isak Merang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service aims to provide knowledge and resolve unresolved problems related to waste management in Punan Dulau Village, Sekatak District, Bulungan Regency. The problem is that there is no landfill in the village so that people in managing household waste tend to throw it into the river and burn it which can cause environmental damage in the village. Therefore, it is important to carry out the Waste Bank Socialization activity as a Strategy to Strengthen Community Participation in Punan Dulau Village, Sekatak District, Bulungan Regency. The method in this service activity uses the method and provides direct examples in the process of making a Waste Bank as a Strategy to Strengthen Community Participation in Punan Dulau Village, Sekatak District, Bulungan Regency. Furthermore, the results of this service activity can provide knowledge to the community about the importance of protecting the environment by creating a Waste Bank in Punan Dulau Village in order to solve the waste problem that has not been resolved so far so that the environment becomes clean and the community gets income from the waste bank.